EPIC JOURNEYS: A COMPARATIVE ANALYSIS OF THE ODYSSEY AND ALPOMISH (International journal of artificial intelligence, 2025)
This article explores the similarities and differences between two great epics of world literature: Homer`s Odyssey from ancient Greece and the Turkic epic Alpomish . By analyzing themes of heroism, loyalty, journey, divine intervention and cultural context, the paper highlights both universal aspects of epic storytelling and the distinctive ways in which different societies express their values through oral tradition. The comparison demonstrates how epics not preserve history and identity but also serve as cultural bridges across time and geography.